PERAN DUKUNGAN REKAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP PERILAKU KEMALASAN SOSIAL DENGAN TURNOVER INTENTION SEBAGAI VARIABEL MEDIASI PADA PT FBA - Raden Aziz Fajar Sazali; Zainul Kisman (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the role of coworker support and organizational commitment on social loafing behavior, with turnover intention as a mediating variable, among employees of PT FBA. The research employed a quantitative approach with a survey method. The sample consisted of 57 respondents selected using Slovin's formula from a total population of 57 employees. The research instrument was a questionnaire using a 5-point Likert scale, and the data were analyzed using Partial Least Squares – Structural Equation Modeling (PLS-SEM). The results indicate that coworker support has no significant effect on turnover intention or social loafing behavior. In contrast, organizational commitment has a negative and significant effect on turnover intention, while turnover intention has a positive and significant effect on social loafing behavior. Mediation analysis reveals that turnover intention does not mediate the relationship between coworker support and social loafing, but significantly mediates the effect of organizational commitment on social loafing. These findings support the Social Exchange Theory, which explains that positive reciprocal relationships strengthen commitment and reduce negative workplace behaviors. The implications of this study emphasize the importance for companies to enhance organizational commitment by reinforcing values, organizational culture, and career development opportunities as efforts to reduce turnover intention and social loafing among employees.